Effect of Tree Plantation Location and Crown Shape on Cross-Ventilation of a Generic Building – A CFD Study - Buddika, J.W.G.; Weerasuriya, A.U.; Lewangamage, C.S.; Xuelin, Z. (University of Jaffna, 2022)
Natural ventilation creates comfortable and healthy indoor environments without consuming energy. However, maintaining adequate natural ventilation is arduous because several factors control its performance, including ambient wind speed and direction, opening configurations, and nearby objects such as vegetation. Among them, the effects of vegetation on natural ventilation are least understood. This study investigated how tree plantation location and crown shape affect the cross-ventilation of a generic building with two openings using Computational Fluid Dynamics (CFD) simulation. The CFD simulations are based on the Reynolds Averaged Navier-Stokes (RANS) equations and use source terms for momentum, turbulent kinetic energy, and turbulent kinetic energy dissipation rate to model the effects of trees on the wind field. The results show a 23% reduction in ventilation rate for trees at a 2H distance upstream of the building (H is the building height) compared to the ventilation rate of a building without trees in its surrounding. Beyond this distance, the ventilation rate deficiency steadily decreases with tree plantation distance and has no reduction for trees planted at 15H upstream of the building. The cuboid-shaped crown causes the highest ventilation rate reduction of 23% compared to the V-shaped (18%), oval (16%), and conical (10%) crowns. This study recommends no trees with cuboidal crowns planting between 1.5H to 2.5H distances upstream of the building and maintaining aerodynamic tree crowns to minimize the adverse effects of trees on the natural ventilation of buildings.
Keywords: Trees; CFD simulation; Crossventilation; Tree crown shape; Tree plantation location